Development of an assertion model of integrity constraints in object-oriented databases - Zaqaibeh, Belal Mohammad (2006)
Object-Oriented Databases (OODBs) have been designed to support large and complex programming projects. The data accuracy, consistency, and integrity in OODBs are extremely important for developers and users. Checking the integrity constraints in OODBs is a fundamental problem in database design. Existing OODB Management Systems (OODBMSs) lack to a capability of an ad-hoc declarative specification of enforcing and maintaining integrity constraints that are appeared among attributes in association, composition, and inheritance hierarchies' relationships. A critical problem in the existing OODBs is that they cannot support User-Defmed Constraints (UDCs) that can be defmed in classes with composition (logical or physical composition) and inherence (single or mUltiple inheritance) hierarchies. Integrity constraints in the current OODBMSs are maintained either by disallowing and rolling back transaction or modifying operations that may produce a violation. The constraints must be maintained in the backward direction along the class composition hierarchy as well as in the forward direction. In this work an Assertion Model of Integrity Constraints (AMIC) is proposed. The AMIC keeps the derivation path along with the attributes' relationships that are derived from association, composition, and inheritance hierarchies. The AMIC techniques are designed to implement the needed functions that are collecting the attributes' relationships and checking the integrity constraints. Moreover, AMIC keeps UDCs with their relationships in both single classes and multilevel classes (intra-class and inter-class). Furthermore, the AMIC can maintain constraints in a single object and a set of distributed objects (intra-object and inter-object). Therefore, this makes the new model extendable and can be integrated with any existing constraints' service. A new technique called Detection Method (DM) isdesigned to check the Object Meta Data (OMD) to detect the constraints violation before it occurs. The AMIC is designed for both Centralized Integrity Maintenance (CIM) and Application-Oriented Integrity Maintenance (AOIM). The AMIC can also enforce and maintain structural and logical integrity constraints, in addition to enforce and maintain redundant, inconsistent, and duplicate constraints.